2008
DOI: 10.1002/jobm.200700325
|View full text |Cite
|
Sign up to set email alerts
|

Influence of signal‐peptide truncations on the functional expression of Escherichia coli γ ‐glutamyltranspeptidase

Abstract: The full-length Escherichia coli gamma -glutamyltranspeptidase (EcGGT) gene and five truncations lacking 33, 51, 54, 60, and 78 bp respectively at the 5' end were prepared by polymerase chain reaction and cloned into the expression vector pQE-30. Isopropyl-beta -D-thiogalactopyranoside induction of E. coli M15 cells bearing the recombinant plasmids resulted in the intracellular production of the expressed proteins, EcGGT, EcGGT/DeltaN11, EcGGT/DeltaN17, EcGGT/DeltaN18, EcGGT/DeltaN20, and EcGGT/DeltaN26. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Earlier, the gene encoding either BlGGT or EcGGT was cloned and over-expressed in recombinant E. coli cells [12,13]. Deletion analysis of both enzymes showed that removal of the signal peptide significantly affects their functional expressions in E. coli [14,15]. To the best of our knowledge, there has been no report dealing with the biophysical characterization of both enzymes, and it is unknown the oligomeric state of these two proteins in solution.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Earlier, the gene encoding either BlGGT or EcGGT was cloned and over-expressed in recombinant E. coli cells [12,13]. Deletion analysis of both enzymes showed that removal of the signal peptide significantly affects their functional expressions in E. coli [14,15]. To the best of our knowledge, there has been no report dealing with the biophysical characterization of both enzymes, and it is unknown the oligomeric state of these two proteins in solution.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, two expression plasmids have been constructed for the functional expressions of BlGGT and EcGGT [14,15]. The molecular mass for the large and small subunits of BlGGT was calculated to be 44,874 and 20,517 Da respectively, and those for EcGGT were 43,030 and 21,237 Da.…”
Section: Electrophoretic Profiles Of the Purified Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from this, N-and C-termini of the intact polypeptide chain (prepro-GGT) of bacterial GGTs were also studied for their importance in autoprocessing. Truncation in the N-terminal region, including the signal peptide, of EcGGT and BlGGT demonstrated that signal peptide is critical for proper enzyme folding and processing (Lin et al, 2008;Lo et al, 2008). For EcGGT, truncation beyond 17 amino acids was found detrimental for maturation, indicating the crucial role of the last nine amino acids of the signal peptide in functional expression of the enzyme (Lo et al, 2008), while in BlGGT, all the truncated mutants except the native enzyme resulted in partial or complete loss of processing, emphasizing again on the importance of signal peptide in the enzyme's folding and maturation (Lin et al, 2008).…”
Section: Molecular Mechanism Of Autoprocessingmentioning
confidence: 99%
“…For efficient intracellular cargo release, GGT has to operate in the cytoplasm instead of its natural reaction space, the periplasm. As suggested by a bioinformatics analysis using the tool SignalP 4.0 [136], the wild type gene encodes a 25 amino acid residues signal peptide at the 5' end of the gene, and previous work with EcGGT suggested interference of the His-tag with the secretion of GGT to the periplasmic space [155]. We tested expression of PnGGT with an N-terminal 6xHis-tag added in front of the signal peptide of the precursor.…”
Section: Cytoplasmic Expression Of Pnggtmentioning
confidence: 99%